Application of RhBMP-2 in Percutaneous Endoscopic Posterior Lumbar Interbody Fusion - Yunsheng Chen; Canhua Xu; Yaohong Wu; Jiangyou Shi; Rongchun Chen (BMC Surgery)
Abstract Background To investigate the application of recombinant human bone morphogenetic protein-2 (RhBMP-2) in Percutaneous Endoscopic Posterior Lumbar Interbody Fusion (PE-PLIF). Materials and methods The study randomly included 102 patients with lumbar spondylosis who underwent PE-PLIF at our hospital from April 2020 to August 2022. Following the random number table method, these subjects were graded as a study group of 51 cases and a control group of 51 cases. Posterior pedicle screw fixation treatment with RhBMP-2 or autologous bone was given respectively. The surgical status and perioperative complications, as well as lumbar spine function before surgery and at 1 and 12 months after surgery [Prolo score and Japanese Orthopaedic Association (JOA) score] of patients in the two groups were observed, and the postoperative fusion rate and cage displacement rate at 1 and 12 months after surgery were compared between the two groups. The degree of vertebral body slippage, intervertebral space height, and changes in quality of life were compared between the two groups before and 12 months after surgery. Results There was no significant difference in hospital stay, surgical time, bleeding volume, and incidence of complications between the two groups (P > 0.05)0.12 months post-operation, the Prolo and JOA scores of both groups largely increased, which were significantly higher in the RhBMP-2 group than the control (P < 0.05). 12 months post-operation, the fusion rate in the RhBMP-2 group was 86.27%, which was significantly higher than that of 54.90% in the control group (P < 0.05). 12 months post-operation, the Cage displacement rate in the RhBMP-2 group was 5.88%, which was lower than that of 21.57% in the control group (P < 0.05). 12 months post-operation, the height of the intervertebral space in both groups largely increased, which was significantly higher in the RhBMP-2 group than in the control (P < 0.05). The degree of vertebral body slippage was significantly reduced in both groups, and the RhBMP-2 group was significantly lower than the control (P < 0.05). The cognitive function, social function, physiological function, and mental health were evidently improved in both groups 12 months post-operation and were significantly higher in the RhBMP-2 group than in the control (P < 0.05). Conclusion RhBMP-2 material in PE-PLIF could significantly restore lumbar function, promote postoperative fusion, reduce Cage displacement and vertebral slippage, accelerate recovery of lumbar intervertebral space, and improve patient quality of life.